Interleukin-13 as a potential biomarker in the management of pediatric asthma – a longitudinal study - Raju, Prasanna; Sundar, Subash; Suresh, Preethi; Vajravelu, Leela Kakithakara; Aravindhan, Vivekanandhan (European Journal of Clinical and Experimental Medicine, 2025)
<h2 class="block-title" style="box-sizing: border-box; font-family: Lato, sans-serif; font-weight: bold; line-height: 1.1; color: #010101; margin-top: 23px; margin-bottom: 11.5px; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Abstract <div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Introduction and aim. Asthma is predominantly a Th2 type hypersensitive disorder, with interleukin (IL) 4 and IL-13 playing a pivotal roles. Interleukin 13 is one of several cytokines that cause persistent inflammation associated with asthma. The aim was to examine the relationship between the response to treatment in asthma and serum IL-13. Material and methods. This study, conducted at the SRM Medical College Hospital and Research Center, in Tamil Nadu, in volved 68 children aged 6 to 12 years of age diagnosed with asthma. The study included medical history, including age of onset of wheezing, history of allergic rhinitis/atopic dermatitis, food allergies, use of inhalational corticosteroids, hospital admissions, and family history. Spirometry was performed, and treatment with inhalational corticosteroids was started according to GINA guidelines. Blood was collected prior to and after 3 months of treatment. Results. A substantial positive correlation was observed between gender and IL-13 levels. An improvement in forced expirato ry volume in the first second (FEV1) was observed after treatment [(74.72% vs 95.05%) (p<0.0001)]. A negative correlation was discovered between IL-13 and FEV1. A statistical significance between IL-13 levels before and after treatment (p=0.005). Conclusion. Inhalational corticosteroids reduced serum IL-13 levels, indicating its role as a prognostic marker in pediatric asthma.